AD Informer Set: Chemical tools to facilitate Alzheimer's disease drug discovery. Issue 1 (20th April 2022) - Potjewyd, Frances M.; Annor‐Gyamfi, Joel K.; Aubé, Jeffrey; Chu, Shaoyou; Conlon, Ivie L.; Frankowski, Kevin J.; Guduru, Shiva K. R.; Hardy, Brian P.; Hopkins, Megan D.; Kinoshita, Chizuru; Kireev, Dmitri B.; Mason, Emily R.; et al.
Abstract: Introduction: The portfolio of novel targets to treat Alzheimer's disease (AD) has been enriched by the Accelerating Medicines Partnership Program for Alzheimer's Disease (AMP AD) program. Methods: Publicly available resources, such as literature and databases, enabled a data‐driven effort to identify existing small molecule modulators for many protein products expressed by the genes nominated by AMP AD and suitable positive control compounds to be included in the set. Compounds contained within the set were manually selected and annotated with associated published, predicted, and/or experimental data. Results: We built an annotated set of 171 small molecule modulators targeting 98 unique proteins that have been nominated by AMP AD consortium members as novel targets for the treatment of AD. The majority of compounds included in the set are inhibitors. These small molecules vary in their quality and should be considered chemical tools that can be used in efforts to validate therapeutic hypotheses, but which will require further optimization. A physical copy of the AD Informer Set can be requested on the Target Enablement to Accelerate Therapy Development for Alzheimer's Disease (TREAT‐AD) website. Discussion: Small molecules that enable target validation are important tools for the translation of novel hypotheses into viable therapeutic strategies for AD.